2011
DOI: 10.1136/jnnp.2010.236018
|View full text |Cite
|
Sign up to set email alerts
|

Differential corticospinal tract degeneration in homozygous 'D90A' SOD-1 ALS and sporadic ALS

Abstract: BackgroundThe homogeneous genotype and stereotyped phenotype of a unique familial form of amyotrophic lateral sclerosis (ALS) (patients homozygous for aspartate-to-alanine mutations in codon 90 (homD90A) superoxide dismutase 1) provides an ideal model for studying genotype/phenotype interactions and pathological features compared with heterogeneous apparently sporadic ALS. The authors aimed to use diffusion tensor tractography to quantify and compare changes in the intracerebral corticospinal tracts of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Both studies showed relatively preserved CST connectivity in mutation carriers compared with sporadic cases. 69,70 DTI changes in nonmotor tracts were reported by a recent study, and have been related to changes in social and emotional processing. 71 Motor network damage has been suggested as a potential marker to track disease progression in ALS, with progressive expansion of white matter damage from the CST to extramotor areas.…”
Section: Behavioural Variant Frontotemporal Dementiamentioning
confidence: 82%
“…Both studies showed relatively preserved CST connectivity in mutation carriers compared with sporadic cases. 69,70 DTI changes in nonmotor tracts were reported by a recent study, and have been related to changes in social and emotional processing. 71 Motor network damage has been suggested as a potential marker to track disease progression in ALS, with progressive expansion of white matter damage from the CST to extramotor areas.…”
Section: Behavioural Variant Frontotemporal Dementiamentioning
confidence: 82%
“…Patients with ALS caused by homozygous Asp90Ala SOD1 mutations had similar CST FA values to healthy controls, whereas patients with sporadic ALS had lower CST FA values, indicating different disease mechanisms between this familial type and sporadic ALS. 83 Some studies have reported decreased FA, 37,76,82,84–87 increased MD, 81,88 and increased axial diffusivity 76,79,89 in the posterior limb of the internal capsule (PLIC). The PLIC contains densely packed CST fibres and might, therefore, be highly sensitive to DTI alterations.…”
Section: Advanced Neuroimaging In Alsmentioning
confidence: 99%
“…The imaging signature of this mutation has been elegantly presented in both symptomatic and pre-symptomatic patient cohorts using diffusion tensor imaging,10 magnetic resonance spectroscopy11 and positron emmission tomography imaging 12…”
Section: Introductionmentioning
confidence: 99%